PENGARUH CORPORATE GOVERNANCE TERHADAP COMPLIANCE OF MANDATORY DISCLOSURE - Faadillah Novia Arisanti (2021)
This study aims to determine the effect of the corporate governance proxied by the board of commissioners, women commissioners, audit committee, audit committee independence, managerial ownership and public ownership on compliance of mandatory disclosure in public companies listed on the Indonesia Stock Exchange. This research is a quantitative type of research using secondary data, namely annual reports and company annual financial reports. The population of this study is the property, real estate, and building construction sector companies listed on the Indonesia Stock Exchange (BEI) during the 2015-2019 period. The research sample was selected using purposive sampling method in order to obtain 12 sample companies. The data were analyzed using multiple linear regression analysis processed with the SPSS version 25 data application. The results showed that the audit committee independence had no effect on compliance of mandatory disclosure, while the board of commissioners, women commissioners, audit committee, managerial ownership and public ownership had an effect on compliance of mandatory disclosure. The implication of this research is that companies, especially in the property, real estate, and building construction sectors can increase the compliance of mandatory disclosure companies by maximizing aspects that have a positive impact on compliance of mandatory disclosure.